The influence of height and edge proximity on balance and reaction time - Weimar, W.; Garner, J.; Campbell, B.; St. Onge, P. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
Previous research has indicated that standing on incline surfaces at heights can attenuate flat surface balance (Wade, Weimar and Davis, 2004). However, research indicating changes in static balance as a result of being on a platform above the ground has received little attention. It is the documentation of the prevalence of falls and the lack of understanding regarding the influence of height on balance that has led to the current study. The purpose of this study is to assess the static balance and information processing demands of standing on an elevated platform. The results of this study will aid in the understanding of the mechanisms that bring about these decrements in balance.